Formulation, Optimization, Physicochemical Characterization, and Pharmacological Evaluation of Aloe vera-Enriched WoundRx Cream Against Excision, Incision, and Burn-Induced Diabetic Wounds in Streptozotocin-Induced Diabetic Wistar Albino Rats - M.Sudha, M.Sudha; Sam, Simi; Toppo, Fedelic Ashish; A Bhaijamal, Rizwan; Nath, Vijay; Poshiya, Krutika Amitkumar; Borawake, Dhanshri; Dingare, Shraddha (Journal of Neonatal Surgery, 2025)
The study aimed to formulate and evaluate a natural topical preparation, named WoundRx Cream, designed specifically to manage excision, incision, and burn wounds in streptozotocin-induced diabetic Wistar albino rats. WoundRx Cream was prepared using natural honey, olive oil, beeswax, and varying concentrations of Aloe vera extract, employing the fusion method. Six formulations (WRF1–WRF6) were characterized based on physical appearance, pH, spreadability, extrudability, and homogeneity. In-vivo wound healing was assessed using excision, incision, and burn wound models in diabetic rats, comparing untreated diabetic controls, normal rats treated with WoundRx Cream, and diabetic rats treated with WoundRx Cream. The pH of all formulations remained skin-compatible (7.36–7.56), while spreadability and extrudability were optimal, increasing with higher Aloe vera concentrations. In-vivo results demonstrated significantly accelerated healing, marked by reduced wound areas and enhanced tissue regeneration, particularly notable in diabetic rats treated with WoundRx Cream compared to diabetic controls (p < 0.05). This enhanced healing effect is attributed to the combined antimicrobial, anti-inflammatory, and regenerative properties of the ingredients, particularly honey and Aloe vera. These findings highlight the promising therapeutic potential of WoundRx Cream as an effective natural intervention for diabetic wound and burn management, supporting its clinical development and future application.